Los efectos del mago de la cara de vidrio en los niños - García García, Luzmila Abigail (2019)
The objective of the research is to identify the effects of television on children, to take preventive measures andintervention, because the future of the company is in the hands of those who are now the weakest. The methodologyused was non-experimental, descriptive, theoretical review of research in the last decade on this issue today. Firstly,based on theoretical explanations need to know that the child population is the most vulnerable to the effects ofthe television, as they are constantly learning agents and imitation. Given the excessive and indiscriminate television exposure were obtained as a result some psychological effects. Being that can significantly impair cognitivefunctions of attention, memory and concentration of children, directly affecting their academic performance (Torresand Garcia, 2009). Also its reflectivity is altered to be much more prone to react violently (Clausell, 2005). Besidestelevision participates in the formation of gender identity, transforms it, makes it known, manipulates it, what difference, in a subtle and often harmless, also, part of the moral and value acquisition is influenced by frequent exposureto television, where entertainment and the most widespread consumption (Veliz, 2005). Finally we conclude that itis essential to the selection and monitoring of television programs to which children are exposed, as the effects theycan cause are of great importance.